Agronomic education: a systemic perspective - Villarruel-Fuentes, Manuel (2022)
Objective. To approach higher agricultural education as a complex structure, explained by the functional relationships between the formative and the executive, under performance contexts that nestle in uncertainty and chaos. Method. The systemic alternative is proposed as a way to reach new rationalities about what higher agricultural education, agronomic training and its professional configuration should be, through a critical and reflexive approach to its professional practices. Results. The guidelines of a new perspective of educational training based on epistemic and theoretical-conceptual schemes, oriented from the complexity of systems, are postulated. Conclusions. Professional practices represent the pinnacle of all disciplinary training, which in the case of the agricultural engineer is manifested through the ways in which he understands the social reality to intervene in it. This dialectical exercise has been pigeonholed in the postulates that science demands, under analytical, linear and predictive schemes. Such approaches to reality have conditioned a paradigmatic paralysis that only allows thinking in conventional forms of academic and professional training, which must be overcome by means of a systemic foundation.